Detection of soil liquefaction from strong motion records. - Kostadinov, Mladen V.
During the recent earthquakes in Japan and the U.S.A. a number of records from liquefied soil sites have been obtained. The ground motion parameters from these sites were studied and several methods for detection of liquefaction from seismic records were developed. The methods, however, focus mainly on the horizontal ground motion and may interpret as liquefaction induced some records from soft soil deposits or records with dominant surface waves, at which sites the phenomenon was not observed. Besides, not all of the available records from liquefied sites were processed. In this paper, after examination of the ability of different types of ground motion parameters to indicate alone soil liquefaction we propose a new liquefaction detection method that simultaneously analyses instantaneous frequency content of the horizontal and the vertical ground acceleration. We also compare performance of the proposed method with that of the other liquefaction detection methods. The computations are carried out using a common data set including records from liquefied and non-liquefied sites. Results show that the frequency related parameters and the proposed method detect more efficiently the occurence of liquefaction from the seismic records.
Keywords: Liquefaction detection; Ground motion parameters; Strong motion records; Mean instantaneous frequency